1986
DOI: 10.1007/bf00321074
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rhesus antibodies (anti-Rh0 (D)) in autoimmune thrombocytopenia: Correlation with response to high dose IgG and the degree of haemolysis

Abstract: We have compared the efficacy of high-dose IgG with that of Rhesus antibodies (anti-Rh0 (D)) in 5 patients with autoimmune thrombocytopenic purpura (3 adults and 2 children). Although only transient, high-dose IgG (0.4 g/kg X 5 days) was effective in all patients (peak values 50-200 X 10(9)/1), whereas anti-Rh0 (D) (11-20 micrograms/kg X 5 days) led to comparable results in only 3 patients (165 X 10(9)/1, 72 X 10(9)/1, 33 X 10(9)/1). This response to anti-Rh0 (D) was neither related to the degree of induced ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…In 1986, Panzer et al compared the effi cacy of IVIg (0.4 g/kg × 5 days) with anti-D (11-20 μg/kg × 5 days) in 5 patients with ITP, 2 of whom were children. 11 The one child with acute ITP who received anti-D had a platelet increase of 11 × 10 9 /L while the child with chronic ITP had a platelet increase of 22 × 10 9 /L. Neither child had a signifi cant decrease in their hemoglobin levels.…”
Section: Anti-d Treatment In Childrenmentioning
confidence: 94%
“…In 1986, Panzer et al compared the effi cacy of IVIg (0.4 g/kg × 5 days) with anti-D (11-20 μg/kg × 5 days) in 5 patients with ITP, 2 of whom were children. 11 The one child with acute ITP who received anti-D had a platelet increase of 11 × 10 9 /L while the child with chronic ITP had a platelet increase of 22 × 10 9 /L. Neither child had a signifi cant decrease in their hemoglobin levels.…”
Section: Anti-d Treatment In Childrenmentioning
confidence: 94%
“…These studies provide valuable information about RhIG in mismatched transfusion inasmuch as they illustrate treatment tolerability. The early studies involved a wide range of doses and administration regimens 48‐53 . Based on earlier work to establish PLT‐sparing efficacy, the total RhIG doses given in these studies were relatively high compared to those used in D‐mismatched transfusion.…”
Section: Lessons From Immune Thrombocytopenic Purpuramentioning
confidence: 99%
“…The early studies involved a wide range of doses and administration regimens. [48][49][50][51][52][53] Based on earlier work to establish PLTsparing efficacy, the total RhIG doses given in these studies were relatively high compared to those used in D-mismatched transfusion. Experiences with these doses are therefore likely to exaggerate the adverse events associated with RhIG administration.…”
Section: Lessons From Immune Thrombocytopenic Purpuramentioning
confidence: 99%
“…1,6 This hypothesis is supported by studies where anti-D was inefficacious in ITP patients lacking the RhD antigen. 7,8 Interestingly, despite the ability of anti-D to lower hemoglobin values in some patients, no relationship is apparent between hemoglobin decreases and responses in ITP [9][10][11] or between erythrocyte sensitization by different doses of anti-D and responses in ITP. 9,10 To add to the complexity, we have recently shown that the TER119 antibody, which mimics the action of anti-D in murine ITP amelioration, [12][13][14] has anti-inflammatory effects in murine arthritis and can prevent disease activity in a murine model of transfusionrelated acute lung injury.…”
Section: Introductionmentioning
confidence: 99%